Pengaruh Lingkungan Kerja, Kepuasan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Rekam Medis RSUD Dr. Haryoto Lumajang - Septiyansah, Achmad; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ Organizational behavior will be closely related to work and various environmental situations, therefore there will be many interrelated behaviors such as employee attendance, employee work tasks, employee productivity, management, employee performance and even employee appearance. HRM is planning, organizing, implementing, coordinating, as supervision of procurement, development, separation of labor and integration in order to achieve organizational goals. Quantitative research is research that uses populations and samples to analyze statistical data to test hypotheses that have been established. previously discovered. The population that will be used as the object of this research is the medical record staff at Dr. Hartyo Lumajang, totaling 36 people. The sampling technique used in this research is a saturated sample, where the entire population is sampled. The work environment, job satisfaction and workload simultaneously have a positive effect on employee performance. The existence of significant differences in research on these variables can be a basis for companies to consider strategies and policies that are more supportive of improving employee performance in the future. Work environment variables have a partial effect on employee performance. The job satisfaction variable has no partial effect on employee performance. The workload variable has no partial effect on employee performance.Â Keywords: Work Environment, Job Satisfaction, Workload